Effects of different cooling treatments on water diffusion, microcirculation, and water content within exercised muscles: Evaluation by magnetic resonance T2-weighted and diffusion-weighted imaging - Yanagisawa, O.; Takahashi, H.; Fukubayashi, T. (Journal of Sports Sciences, 2010)
In this study, we determined the effects of different cooling treatments on exercised muscles. Seven adults underwent four post-exercise treatments (20-min ice-bag application, 60-min gel-pack application at 10°C and 17°C, and non-cooling treatment) with at least 1 week between treatments. Magnetic resonance diffusion- and T2-weighted images were obtained to calculate the apparent diffusion coefficients (apparent diffusion coefficient 1, which reflects intramuscular water diffusion and microcirculation, and apparent diffusion coefficient 2, which is approximately equal to the true diffusion coefficient that excludes as much of the effect of intramuscular microcirculation as possible) and the T2 values (intramuscular water content level) of the ankle dorsiflexors, respectively, before and after ankle dorsiflexion exercise and after post-exercise treatment. The T2 values increased significantly after exercise and returned to pre-exercise values after each treatment; no significant differences were observed among the four post-exercise treatments. Both apparent diffusion coefficients also increased significantly after exercise and decreased significantly after the three cooling treatments; no significant difference was detected among the three cooling treatments. Local cooling suppresses both water diffusion and microcirculation within exercised muscles. Moreover, although the treatment time was longer, adequate cooling effects could be achieved using the gel-pack applications at relatively mild cooling temperatures.